Pengaruh Kualitas Layanan terhadap Kepuasan Nasabah ( Studi pada Nasabah Pemegang Tabungan Simpeda Bank Kalsel Cabang Tanjung ) - Fitri Hernadi; Dwi Wahyu Artiningsih; Maryono Maryono (Universitas Lambung Mangkurat, 2014)
Purpose of the research is to knowing and analyze quality of service is measured based on the physical aspects of the service and non-physical aspects have an influence of the partially on customer satisfaction, it has an influence of simultaneously, and from the two aspects, which aspect is more dominant on customer satisfaction holder Simpeda Savings Bank Kalse Branch Tanjung.The research approach used is quantitative with explanatory research type and research location is on Bank Kalsel Branch Tanjung. The population of research is customer holders Bank Kalsel Branch Tanjung with a total sample of 100 respondents. Analysis of the data using Multiple Linear Regression analysis techniques, to test the influence of simultaneous use test F and to test partial influence used T Test at significance level 0.05.Results of research proved that the quality of service which measured base on physical aspect and non-physical aspect have an effect partially where the data processed using the T test found that the number T count for non-physical aspects of 2,522 and T count for the physical aspect of 2,821 while the T table known for 1.661 or if it compared to the count T > T table can be concluded that there is a partial influence both aspects on customer satisfaction. Physical aspects and non-physical aspects also influence simultaneously on customer satisfaction which evidenced by the results of the F test where from the data processing obtained value of F count of 35 455 and the F table at 3,090 so F count > F table or it can be concluded that the physical aspect and the non-physical aspects have a simultaneous influence on customer satisfaction. The physical aspect is the dominant aspect because it has value T count is higher than T count the non-physical aspects which prove that the physical aspect has a dominant influence on customer satisfaction holder Simpeda Savings Bank Kalsel Branch Tanjung.From the result of research found that the physical aspect is dominant aspects that give an influence to customer satisfaction, different from results of previous research where the non-physical aspect is a more dominant aspect in influencing customer satisfaction. Keywords: Service Quality, Customer Satisfaction